USING ADVERTISEMENT IN ENGLISH LANGUAGE TEACHING TO INCREASE LISTENING COMPREHENSION SKILL AT JUNIOR HIGH SCHOOL 3 BONTOMARANNU - Nur Fitri Al Fiana; Andi Tenri Ampa; Muhammad Zia UlHaq (English Language Teaching Methodology, 2022)
This research aimed at finding out the increase of students’ listening skill in terms of accuracy of answer by using Advertisement at eighth Grade students of SMP Negeri 3 Bontomarannu. The Researcher used a quantitative method with one group pre-test and post-test; the researcher used a pre-experimental design. The findings showed that Advertisement was effective to increase students’ listening skill. It was supported by the students mean score in pre-test was 45.00 and it was increase to be 84.09 in post-test and the value of t-test was higher rather than the value of t-table (6.919 > 1.720). Therefore, the Alternative Hypothesis was accepted and the Null hypothesis was rejected. Based on the result analysis, the researcher concluded that advertisement increase students’ listening skill